PENINGKATAN PEMAHAMAN HUKUM MASYARAKAT DAN PENCEGAHAN KEKERASAN DALAM RUMAH TANGGA DI DESA AMBOLOLI KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Fitriah Faisal; Endah Widyastuti; Wa Ode Zuliarti; Rahman Hasima; Ahmad Firman Tarta (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2023)
This Community Service Activity is entitled "Increasing Knowledge and Preventing Domestic Violence in Ambololi Village, Konda District, South Konawe Regency". The aim of this Community service activity is to increase public knowledge of domestic violence, so that it can achieve the objectives of the establishment of Law no. 23 of 2004 namely the Elimination of Domestic Violence (KDRT). The stages of activities that will be carried out are as follows: (a) preparation stage includes: survey; stabilization and determination of locations and targets; preparation of training materials/materials, which include: presentation materials, powerpoint slides, (b) the implementation stage includes: (1) Explanation of material regarding the concept of domestic violence, the subject of protection and how to report cases of domestic violence based on statutory provisions as follows a form of education for partner village communities, (2) this legal education activity is carried out by a community service team from the university community involving students. The methods used during the process of community service activities include: (a) the lecture method which is chosen to provide direct explanations about the extension material, (b) the Question and answer method which allows the community to gain as much knowledge as possible about the extension material. Based on the results of this activities carried out in village, it can be concluded that this activity was attended by 30 people consisting of the community and village officials. With legal education, it can increase the knowledge and understanding of the Ambololi Village community regarding the importance of preventing domestic violence, so that it has an impact. to the formation of legal awareness in the community to jointly realize the spirit of Law no. 23 of 2004, namely the elimination of domestic violence.